2015
DOI: 10.15850/amj.v2n4.642
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Body Mass Index and Body Fat Percentage

Abstract: Background: Body mass index (BMI) has been used to determine the nutritional status which is classified into low, normal, overweight or obese. The BMI only shows a comparison of height and weight instead of body composition which consists of fat mass and fat-free mass. Most of people assumed that BMI overage means fat mass overage as well, yet it does not occur in all cases. This study was conducted to measure the correlation between BMI and body fat percentage. Methods: An analytical study was conducted to 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
(13 reference statements)
1
6
0
Order By: Relevance
“…However, Pearson's correlation coefficients were found to be low ( r = −0.20 for men and r = −0.47 for women) when compared to previous studies that utilized other obesity evaluation tools with BF% [16, 18, 19]. In 1996, Gallagher et al [20] studied the relationship between BMI and BF% and reported values of r = 0.58 for men and r = 0.72 for women.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…However, Pearson's correlation coefficients were found to be low ( r = −0.20 for men and r = −0.47 for women) when compared to previous studies that utilized other obesity evaluation tools with BF% [16, 18, 19]. In 1996, Gallagher et al [20] studied the relationship between BMI and BF% and reported values of r = 0.58 for men and r = 0.72 for women.…”
Section: Discussionmentioning
confidence: 86%
“…In 1996, Gallagher et al [ 20 ] studied the relationship between BMI and BF% and reported values of r = 0.58 for men and r = 0.72 for women. Ilman et al [ 19 ] have reported r = 0.85 for men and r = 0.83 for women. Each study described a distinct BF% prediction model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The arm to height ratio can negatively affect RTs but not in a linear fashion [ 46 ]. The BMI has a positive correlation with fat percentage [ 47 , 48 ] and a complex correlation with muscle mass, handgrip strength and endurance [ 49 ]. All these factors can affect RTs individually, with a generally positive correlation between fat percentage and VRT and a negative correlation between muscle function indices and RTs [ 44 , 50 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The South Asian have higher percent body fat (Misra et al, 2014) generally, while comparing with gender reference women significantly greater percent body fat as compared to male (Dias et al, 2016;Ilman, Zuhairini, & Siddiq, 2016;Juntaping et al, 2017;Jackson et al, 2002), but comparing within same gender the Asian women have higher body fat as compared to white (Deurenberg, Yap, & Van Staveren, 1998;Küpper et al, 1998;, Chinese (Ntuk et al, 2014), Norwegian (Falch, & Steihaug, 2000), and American women (Kamath et al, 1999).…”
Section: Introductionmentioning
confidence: 99%